pneumonia in childern admitted with lower respiratory tract infections.... A hospital based study - Al janabi, Muhi K.; Al hashimi, Ban A.; sultan, Alhan H. (Journal of the Faculty of Medicine Baghdad, 2013)
Summary:Background: Pneumonia is a common form of lower respiratory tract infection (LRTI) in children under five years of age and it is the leading cause of morbidity and mortality in this age group. Early management is important in decreasing its complications and mortality.Methods: A cross sectional study of 100 patients, their ages ranged from 2 months to 5 years. They were admitted to Children Welfare Teaching Hospital Medical City–Baghdad in a period from 7th of November 2010 to 5th of May 2011, suffering from Lower Respiratory Tract Infections (fever, cough and tachypnea) and classified into two groups according to chest radiograph (CXR) findings, those with a patch (pneumonia) and others with normal or hyper inflated CXR. The possibility of various demographic and clinical symptoms and signs to predict the presence or absence of the patch were evaluated.Results: From a total of 100 patients enrolled in this study, 42%had a patch and 58% had normal or hyperinflated CXR. Older age, male gender, longer duration of hospitalization, high level of paternal education and family history of same disease are significantly associated with the presence of patch. Signs and symptoms like deterioration in the level of consciousness, lung crepitation and decrease in air entry and convulsion are significantly associated with the presence of the patch.Conclusion: Pneumonia is frequent in children with LRTI. Presence of convulsions, deterioration in the level of consciousness, lung crepitation and decrease in air entry in a child with LRTI may raise the suspicion of having pneumonia. Factors like older age, male gender, and high level of paternal education were associated with increase the susceptibility to have pneumonia in children with LRTI. Key word: children; predictors; pneumonia.